Differential shear wave attenuation property of the Kumaon and Garhwal Himalaya, India in terms of shallow shear wave velocity profiles - Bhardwaj, Parul; Joshi, A; Pandey, Mohit; Bhargav, Mrityunjay (Journal of Earth System Science, 2022)
The Uttarakhand Himalaya which lies in the central seismic gap region of Himalaya is divided into the Garhwal and Kumaon Himalayas. Several studies by different workers confirm differential attenuation behaviour of shear wave in the Garhwal and Kumaon Himalaya. In the present study, the shear wave velocity structure has been estimated using strong motion data and ambient noise data recorded in these two regions. In this study, the SH-wave transfer function of the Haskell–Thompson matrix has been calculated using the initial shear wave velocity model selected through the genetic algorithm (GA) approach and is compared with the HVSR curve obtained from strong motion data and ambient noise data. The total number of 38 strong motion records together with the ambient noise record that lies between the MBT and MCT has been used in the present study. The obtained velocity model has been used to prepare three-dimensional velocity surrounding Askot which confirms the presence of klippe in the region. The average shear wave velocity at different depths has been calculated for all investigated data in Garhwal and Kumaon Himalaya. The comparison of the average shear wave velocity model obtained for the Garhwal and Kumaon regions shows that the shear wave velocity in Garhwal Himalaya is comparatively higher than that in the Kumaon Himalaya. The average shear wave velocity at 30 m depth in Garhwal and Kumaon Himalaya is found to be in the range of 274–577 and 233–531 m/s, respectively. The results show that the region of Garhwal and Kumaon Himalaya that was taken in the present study fall under the C and D type site category according to National Earthquake Hazards Reduction Program (NEHRP) site classification. Low-velocity stiff soil mostly covers the Kumaon Himalaya region while in Garhwal Himalaya, the region is covered with high-velocity soft rocks. Most of the regions in Kumaon Himalaya are covered by high predominant frequency values as compared to that in the Garhwal Himalaya which indicates the presence of thin sediment layers overlying the basement rocks in Kumaon Himalaya. The average predominant frequency in Garhwal and Kumaon Himalaya ranges from 2.4–15 and 2.5–18.4 Hz, respectively. The anelastic attenuation factor has also been calculated using obtained shear wave quality factor and obtained shear wave velocities at different depths which supports the high attenuation of seismic energy in Kumaon Himalaya as compared to the Garhwal Himalaya.